A “New” Definition of Waste: How to See and UnderstandToyota Production System Main Concept Beyond a List and in Any Kind of Business - Vasquez, Bruno Luiz [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2025)
A latent difficulty of Lean practitioners is to face the challenge of abstracting the concept of waste when dealing with non-manufacturing contexts, such as office work and services. Terms like production - as in overproduction -, transportation, stock/inventory and defective are commonly regarded and interpreted as manufacturing concepts, and not by its generic meaning and etymology, opening a path for the rising of unnecessary variations and complications of TPS, such as Lean Office, Lean Healthcare, etc. The concept of the “seven wastes” in the context of manufacturing efficiency is, nowadays, widely known and diffused. However, it is now known that there were several interpretation errors and negligence in translation and transposition of the Japanese concepts by Western researchers and management authors inside the naturally convoluted process of knowledge transfer. Following this path of investigation, I have found that critical to the subject of promoting waste elimination, is the fact that first definitions do not include a list of seven types, nor any list whatsoever. Hence, the purpose of this article is to analyze two of the earliest, pre-Lean, official sources of the concept of waste in the context of TPS. Then, propose its use as a more effective definition, by demonstrating how it simplifies the waste identification and waste elimination processes beyond work or business type borders. The resource view of the concept of waste found in TPS removes the unintended barriers created by its industrial origins, and reinstate the universal management system perspective of Taiichi Ohno. By adopting this perspective, there is no need to transpose or translate terms, nor to create extra confusion that benefits the consulting and training companies only. Resource is a more neutral term, and through the right stimulus, leads to one of the most needed skills for companies that desire to make cost reduction a routine: employees that are critical thinkers and that go beyond boundaries. By the means of this “new” definition, an office worker can easily understand that a report that contains an error demands a need for surplus working hours for correction (a resource with monetary value and thus, contributing to the overall cost) that otherwise - if the work method could prevent such error - would be avoided. And this is nothing more than the industrial equivalent waste generated by producing defects.